PENGARUH VISUAL AESTHETICS DAN PRESENTATION MODALITY TERHADAP INFORMATION CREDIBILITY, CONSUMER TRUST DAN PURCHASE INTENTION - Antariksa Wibawa Natanegara (Jurnal Bisnis dan Keuangan, 2021)
This study analyzes how visual aesthetics and presentation modality influence information credibility, consumer trust and purchase intention on food content. This research uses a quantitative approach and belongs to the category of causal studies. The sampling technique used is non probability sampling. The sample of this research is people who actively use Instagram, follow culinary accounts, have bought food products on Instagram. Data collection techniques through surveys with a questionnaire that uses a five-‐level Likert scale. The questionnaire was distributed via an electronic link using google form. The analysistechnique used is MANOVA and SEM. The results of this study stated that visual aesthetic and presentation modality affect information credibility and consumer trust, then information credibility and consumer trust affect purchase intention.